The influence of financial service factors on entrepreneurial competencies and business success among women entrepreneurs: a case study of Sahabat Amanah Ikhtiar Malaysia / Mohamad Hanif Baharudin ... [et al.] - Baharudin, Mohamad Hanif; Ramzi, Mohammad Ikram; Md Salleh, Mohamad Sayuti; Wan Mohamad, Wan Mohd Firdaus; Zubir, Ahmad Mudzfir (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
Malaysian government is currently pushing for and encouraging women involvement in entrepreneurship, which will ultimately stimulate the country's economy. Furthermore, concerns regarding the survival and sustainability of business and women entrepreneurs have been brought up by the leadership, despite governmental recognition. The journey towards business success among these women entrepreneurs, especially those from developing countries, may be further complicated by the lack of competencies and the need for continuous assistance. Thus, the present study is aiming to propose a model for women business success, aligning with the role of microfinance as a provider of financial service and entrepreneurial competencies. A total of 392 women entrepreneurs under the Amanah Ikhtiar Malaysia (AIM) scheme have been involved in this study. It has utilised 6 dimensions of entrepreneurial competencies, which are: strategic competencies, commitment competencies, organizing competencies, relationship competencies, commitment competencies, opportunity competencies and conceptual competencies. Meanwhile, microfinance factors like the financial factor have been used as a moderating effect, whereby their respective dimensions are credit and saving. Structural Equation Modeling (SEM) has been employed as the main statistical technique in this study. Overall, the study has found that only four of the independent variables (i.e. elements of entrepreneurial competencies), namely relationship, opportunity, organizing and commitment competencies have significant relationships with women's business success. The remaining 2 domains, strategic competencies and conceptual competencies have revealed to be not significant. Furthermore, the financial factors fully moderated the relationship between entrepreneurial competencies and business success. The findings are likely to be useful to SMEs, as they have highlighted the necessity of focusing on training to yield increased effectiveness. In addition, the impact of microfinance factors will assist women entrepreneurs to becoming successful in their businesses. The model from this study will also further contribute towards the development of literature review related to the favourable outcome for women entrepreneurs.